Tutorial link, a challenge in teacher's formation - Michelle Monterrosas Brisson; Teresa de Jesús Negrete Arteaga (Ministerio de Educación, Dirección General de Educación Superior, 2018)
This article shows the results of an investigation-intervention about the establishment of the link tutor-tutored, and its repercussion in the process of professional formation of students of the Faculty of Biological Sciences of the Autonomous University of the State of Morelos, Mexico. The investigation-intervention was carried out between 2016 and 2017 with teachers and students of the Biology program. The investigation process consisted in doing in-depth interviews, such as a dramatization exercise, to enquire about what the involved actors have to say. The focal point to analyse the link, is Michel Foucault's device knowledge-power-subjectivity, such as the tensions that come into play in the exercise of tutoring, between what is instituted and what is instituting. This work is not intended to clarify the role of the tutor regarding the instituted policies, on the contrary it questions them and opens the discussion about its effects when the link is diminished as can be observed along the investigation-intervention findings.